1999
DOI: 10.1097/00005392-199909000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Dysfunction in Children With Refractory Monosymptomatic Primary Nocturnal Enuresis

Abstract: Abnormal bladder function, including small functional capacity, instability during sleep and marked detrusor hypercontractility, was common in our enuretic children in whom treatment failed. More importantly, nocturnal enuresis may be the only presenting symptom and there may be a response to desmopressin with a decreased number of wet nights even in cases of significant underlying bladder dysfunction. These findings may have important implications for our management strategy for monosymptomatic primary noctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 19 publications
2
74
0
4
Order By: Relevance
“…12,13 The MNE population has been divided into polyuric and nonpolyuric with the latter considered detrusor-dependent with small functional bladder capacity 1,6,14 or minor bladder dysfunction, which is common in daytime symptomatic enuretic patients. 15 In the polyuric group of MNE vasopressin has been advocated, with an overall positive response rate ranging from 50% to 75%. 13,14 Not all polyuric bedwetters are vasopressin responders, and so other factors have been suggested as being responsible for nocturnal bedwetting.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The MNE population has been divided into polyuric and nonpolyuric with the latter considered detrusor-dependent with small functional bladder capacity 1,6,14 or minor bladder dysfunction, which is common in daytime symptomatic enuretic patients. 15 In the polyuric group of MNE vasopressin has been advocated, with an overall positive response rate ranging from 50% to 75%. 13,14 Not all polyuric bedwetters are vasopressin responders, and so other factors have been suggested as being responsible for nocturnal bedwetting.…”
Section: Discussionmentioning
confidence: 99%
“…Although urine output and bladder capacity were not measured in the present study, the results may nevertheless be useful in understanding the pathophysiology of enuresis. We intended to exclude bladder problems by assessing the history, but apparently bladder problems may not always be easy to detect, or detrusor overactivity might occur only during sleep [20].…”
Section: Discussionmentioning
confidence: 99%
“…Yeung performed ambulatory cystometries and found that bladder overactivity is an important cause of therapyresistant nocturnal enuresis. 8 Newer theories point to the role of the central nervous system in bedwetting. Parents of children who wet the bed often claim that they are "deep sleepers."…”
Section: Why Does Nocturnal Enuresis Occur?mentioning
confidence: 99%